PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPAS MATERI ENERGI DALAM KEHIDUPAN SEHARI-HARI SISWA KELAS IV SD - Wedyawati, Nelly; Febriani, Viona; Warkintin, Warkintin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to develop interactive video learning media based on local culture to improve the fourth grade of students learning outcomes, especially energy in everyday life thema. This is a research and development using the ADDIE method which is analysis, design, development, implementation, and evaluation. The research subjects involved 110 students from several elementary schools in Sintang. The data collected through expert validation, user responses, as well as various statistical tests such as validity, reliability and hypothesis testing. The research results showed that the media developed was considered very feasible by media experts (85.93%) and appropriate by material experts (75%). Student and teacher responses to this media were also good, with scores of 80.36% and 77% respectively in the wide-scale test. The increase in student learning outcomes can be seen from the pretest score of 28.81% and posttest 78.36%, so this media has proven to be effective in improving student learning outcomes.